Pengaruh Hasil Belajar Pendidikan Agama Islam Terhadap Akhlak Mahmudah Di MTS Al-Umm Medan Marelan - Minta Ito Hasibuan; Hotni Sari Harahap; Yulia Warda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of Islamic Religious Education (IRE) learning outcomes on students' noble character (akhlak mahmudah) at MTs Al-Umm Medan Marelan. Using a quantitative correlational approach, the research involved 60 students as the sample. Data were collected through tests to measure IRE learning outcomes and questionnaires to assess students’ moral behavior. The results showed that there is a significant positive relationship between IRE achievement and the development of akhlak mahmudah. The regression analysis revealed that 32.6% of the variation in students’ moral behavior is influenced by their IRE learning outcomes. This finding indicates that while religious education contributes to character development, other external factors such as family environment, peer influence, and social context also play a role. The study highlights the importance of integrating moral values into the IRE curriculum through affective learning, religious habituation, and teacher role modeling. It is recommended that schools adopt a holistic educational approach to strengthen both intellectual and moral dimensions of students' development.